Door Opener or Waste of Time? The Effects of Student Internships on Labor Market Outcomes - Thomas Siedler; Nils Saniter; Mathias Schumann (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2016)
This paper studies the causal effect of student internship experience on wages later in life. We use variation in the introduction and abolition of mandatory internships at German universities as an instrument for completing an internship while studying. Employing longitudinal data from graduate surveys, we find positive and significant wage returns of about six percent in both OLS and IV regressions. The positive returns are particularly pronounced for individuals and areas of study that are characterized by a weak labor market orientation, and for graduates in humanities and social sciences.
Keywords: I23; A23; J31; 330